Dynamic of nitrogen and dissolved organic carbon in an alpine forested catchment: atmospheric deposition and soil solution trends - Raffaella Balestrini (Nature Conservation, 2019)
A number of studies have reported decreasing trends of acidifying and N deposition inputs to forest areas throughout Europe and the USA in recent decades. There is a need to assess the responses of the ecosystem to declining atmospheric pollution by monitoring the variations of chemical species in the various compartments of the forest ecosystem on a long temporal scale. In this study, we report on patterns and trends in throughfall deposition concentrations of inorganic N, dissolved organic N (DON) and C (DOC) over a 20-year (1995–2015) period in the LTER site -Val Masino (1190 m a.s.l.), a spruce forest, in the Central Italian Alps. The same chemical species were studied in the litter floor leachates and mineral soil solution, at three different depths (15, 40 and 70 cm), over a 10-year period (2005–2015). Inorganic N concentration was drastically reduced as throughfall and litter floor leachates percolated through the topsoil, where the measured mean values (2 µeq L-1) were much lower than the critical limits established for coniferous stands (14 µeq L-1). The seasonal temperature dependence of throughfall DOC and DON concentration suggests that the microbial community living on the needles was the main source of dissolved organic matter. Most of DOC and DON infiltrating from the litter floor were retained in the mineral soil. The rainfall amount was the only climatic factor exerting a control on DOC and N compounds in throughfall and forest floor leachates over a decadal period. Concentration of SO4 and NO3 declined by 50% and 26% respectively in throughfall deposition. Trends of NO3 and SO4 in forest floor leachates and mineral soil solution mirrored declining depositions. No trends in both DON and DOC concentration and in DOC/DON ratio in soil solutions were observed. These outcomes suggest that the declining NO3 and SO4 atmospheric inputs did not influence the dynamic of DON and DOC in the Val Masino forest. The results of this study are particularly relevant, as they are based on a comprehensive survey of all the main compartments of the forest ecosystem. Moreover, this kind of long-term research has rarely been carried out in the Alpine region.